ANALISIS PENGARUH HARGA, KUALITAS PRODUK, DAN KESADARAN MEREK TERHADAP KEPUASAN PELANGGAN DAN IMPLIKASINYA TERHADAP LOYALITAS PELANGGAN (Studi pada Mahasiswa Pengguna Kartu Simpati di Wilayah Kota Semarang) - Ramadhani, Reinisa; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2016)
This research is motivated by a decrease in the level of customer satisfaction with Simpati cards that indicate a decline in consumer loyalty to the Simpati Card. With the existing problems, this study aimed to examine the effect of pricing, product quality and brand awareness on consumer loyalty premises customer satisfaction sebgai intervening variables.This research was conducted by using multiple regression analysis. Samples in this study of 100 respondents Simpati Card users in the city of Semarang. In this penenlitian there are models with price, product quality and brand awareness as independent variables, as intervening customer satisfaction, and customer loyalty as the dependent variable. By using the software SPSS for windows.The results of research showing that price, the consumer quality, and brand awareness positive and significant impact on consumer satisfaction with the results = 0,198 Â + 0,451 Â + 0,336 s well as consumer satisfaction is positively and significantly with the results = 0,844